K0.5Na0.5NbO3‐Based Lead‐Free Transparent Electro‐Optic Ceramics Prepared by Pressureless Sintering. Issue 11 (24th August 2013) - Li, Faliang; Kwok, Kin‐Wing
Abstract : Transparent lead‐free electro‐optic (EO) ceramics (K0.5 Na0.5 )0.9 Li0.1 Nb0.9 Bi0.1 O3 have been fabricated by pressureless sintering. The ceramics have a fine‐grained structure and cubic‐like symmetry. The comodification with Li and Bi induces a diffuse phase transition, causing the ceramics become relaxor‐like and contain polar nanoregions. Our results reveal that excess Bi2 O3 can further enhance the changes in the crystal structure and dielectric behavior of the ceramics, causing them become more cubic‐like and more relaxor‐like, respectively. These can reduce the light scattering arisen from birefringence and domain walls, and thus improving the optical properties. For the ceramics added with 4 and 6 mol% excess Bi2 O3, the optical transmittance reaches a high value of 60%–70% in the near‐infrared region. The ceramics also exhibits a good linear EO response, giving an effective EO coefficient of 30–40 pm/V.